Non-muslim Schooling in Kosovo during the Abdulhamit II Era and the Policy of Ottoman Government - (:unkn) unknown (EDAM, 2013)
The purpose of this study was to uncover real importance and volume of schooling interlaced with political practices through placing the education in a pragmatic position in forming national epistemologies and political ambitions by non-muslims who desire to establish a geography by virtue of having specific national histories, cultures, languages, religions, literatures, and broad and deep ententes with Ottoman management in the final stage of the government. Within this framework, it was tried to interpret the events, institutions, and individuals concerning the subject between 1876 and 1909 in their own conditions as they were by means of vertical method and historical research pattern.
Keywords: Ottoman Empire; Abdulhamid II; Kosovo; Non-Muslim; Foreign Intervention; Orthodox